2012
DOI: 10.1093/mp/sss025
|View full text |Cite
|
Sign up to set email alerts
|

UVR8 Mediates UV-B-Induced Arabidopsis Defense Responses against Botrytis cinerea by Controlling Sinapate Accumulation

Abstract: Light is emerging as a central regulator of plant immune responses against herbivores and pathogens. Solar UV-B radiation plays an important role as a positive modulator of plant defense. However, since UV-B photons can interact with a wide spectrum of molecular targets in plant tissues, the mechanisms that mediate their effects on plant defense have remained elusive. Here, we show that ecologically meaningful doses of UV-B radiation increase Arabidopsis resistance to the necrotrophic fungus Botrytis cinerea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 89 publications
6
164
0
1
Order By: Relevance
“…1). UV-B radiation has also been reported to increase plant resistance to microbial pathogens (Gunasekera et al, 1997;Wargent et al, 2006;Gunasekera and Paul, 2007;Kunz et al, 2008;Demkura and Ballaré, 2012) and can interact with the plant to modify the composition of microbial communities in the phyllosphere (Kadivar and Stapleton, 2003;Balint-Kurti et al, 2010). Treatment with unnaturally high doses of UV-B radiation, or with UV wavelengths not present in the daylight spectrum (UV-C, l , 280 nm), has also been reported to activate defense-related pathways in several species (Bridge and Klarman, 1973;Brederode et al, 1991;Conconi et al, 1996;Mert-Turk et al, 2003;Glawischnig, 2007); however, the ecological significance of these responses is not clear.…”
Section: Uv-b and Uvr8mentioning
confidence: 99%
See 1 more Smart Citation
“…1). UV-B radiation has also been reported to increase plant resistance to microbial pathogens (Gunasekera et al, 1997;Wargent et al, 2006;Gunasekera and Paul, 2007;Kunz et al, 2008;Demkura and Ballaré, 2012) and can interact with the plant to modify the composition of microbial communities in the phyllosphere (Kadivar and Stapleton, 2003;Balint-Kurti et al, 2010). Treatment with unnaturally high doses of UV-B radiation, or with UV wavelengths not present in the daylight spectrum (UV-C, l , 280 nm), has also been reported to activate defense-related pathways in several species (Bridge and Klarman, 1973;Brederode et al, 1991;Conconi et al, 1996;Mert-Turk et al, 2003;Glawischnig, 2007); however, the ecological significance of these responses is not clear.…”
Section: Uv-b and Uvr8mentioning
confidence: 99%
“…(Stratmann et al, 2000;Izaguirre et al, 2003;Demkura et al, 2010). However, synergistic effects of UV-B and JA elicitation have not been observed for several classic markers of the JA response in Arabidopsis (Arabidopsis thaliana; Demkura and Ballaré, 2012). Similarly, mixed results have been obtained regarding the effects of UV-B radiation on JA accumulation (A-H- Mackerness et al, 1999;Demkura et al, 2010).…”
Section: Uv-b and Uvr8mentioning
confidence: 99%
“…Specific UV-B perception is facilitated by the photoreceptor UV RESISTANCE LOCUS 8 (UVR8) identified only recently in Arabidopsis (7). In agreement with its photoreceptor function, uvr8 null mutants show a strongly reduced response to UV-B (8)(9)(10)(11), which even is absent under conditions specifically activating UV-B photoreceptor responses (4). In contrast, UV-B stress responses are not affected per se in uvr8 mutants (12).…”
mentioning
confidence: 91%
“…Studies have shown that UVR8 can stimulate the biosynthesis of acid salt enhanced plant resistance to Botrytis cinerea [8], Botrytis cinerea [9] is an important disease of strawberry harm of protected cultivation, the control methods mainly rely on chemical agents, long-term use of this kind of medicament not only makes strawberry resistance to Botrytis cinerea, and serious pollution the environment is not conducive to agricultural products, production and sales. If the overexpression of strawberry FaUVR8 can be confirmed, the plant resistance to Botrytis cinerea can be significantly improved, which will be of great significance in the production practice.…”
Section: Discussionmentioning
confidence: 99%